Identification and Optimization of Ecological Restoration Areas Coupled with Ecosystem Service Supply and Demand in the Northern Shaanxi Loess Plateau - Yongxiu Sun; Yue Ren; Shiliang Liu; Wenxin Chen; Yingjie Xu; Jingzhi Xu; Panpan Dang; Zhirui Niu; Xiaoling Xu; Fangyan Cheng (Land)
Ecological restoration is crucial for maintaining national ecological security. Scientific and reasonable identification of key ecological restoration areas is a difficult problem facing the current national spatial planning. This study evaluated ecosystem service (ES) supply, demand, and their spatio-temporal characteristics in the Northern Shaanxi Loess Plateau (NSLP). A coupling coordination degree (CCD) model was applied to study the interactive relationship between ES supply and demand. The improved ant colony optimization (ACO) model was applied to explore the priority areas of ecological restoration. The results showed that ES supply, demand, and balance had significant spatial differences. Higher ES supply areas were distributed in the south, and higher demand areas were located in the central and northern parts. The balance of ecosystem service exhibited a similar increasing trend to the supply of ES from north to south. Temporally, the supply, demand and balance of ES showed distinct time-varying characteristics across different types of services. Total ES supply decreased from 2000 to 2020, while total ES demand and balance first declined and then rose. Moreover, total ES balance showed a significant decreasing trend in 21.22% of regions in the NSLP. Furthermore, the CCD results showed that about 82% of the regions had a disorder status in 2000, while about 90% of the regions had a coordination status from 2010 to 2020. This also implied that the coupling coordination degree in most regions gradually improved from 2000 to 2020. Finally, four ES enhancement priorities were further identified from the perspectives of enhancing ES supply capacity. Ecological restoration prioritization of different ES enhancements showed significant spatial variations, with the top 15% of the ecological restoration area located in the east–central and west–central regions. The top 5% of total ecosystem services can bring 2,470,400 yuan in ecological benefits. This research can offer scientific and theoretical guidance as well as a reference for decision-makers to undertake ecological restoration efforts.